Critical Reading Associate with Education and Role of School Librarian - Ayşenur Güneş; Fatih Güneş (Türk Kütüphaneciliği)
This study’s aim increase student’s success level and emphasize to critical reading importance so introduce school librarian’s responsibilities in this subject. This study’s scope gain the critical reading skills to individuals and school librarian’s responsibilities about being society where are people who are thinking, critic, reading. In this context our study’s hypotheses are “School librarians are advisor about gaining critical reading skills”, “ School librarian speed up gaining critical reading skills process” and “ School librarians are effective about gaining critical reading skills”. This study was realized by description method. By literature survey and evaluations as a result school librarians are effective about gaining critical reading skills and they are advisor teacher about gaining critical reading skills.